PERCEIVED VALUE SEBAGAI MEDIASI PENGARUH E-SERVICESCAPE TERHADAP LOYALITAS PELANGGAN - Faiza, Nur; Rachman, Riza (Relawan Jurnal Indonesia, 2023)
The online shop has become a popular trend in shopping for various groups of people in Indonesia, providing convenience for consumers to make transactions from anywhere. The purpose of this research is to empirically examine and prove the influence of e-servicescape on shopping on the Shopee marketplace in increasing customer loyalty, test the influence of e-servicescape in increasing perceived value, examine the influence of perceived value in increasing customer loyalty, and test the magnitude of the influence of e-servicescape on customer loyalty through perceived value as a mediating variable. The research method used quantitative methods by conducting a survey of 170 Shopee marketplace users in East Java. The research data were analyzed using Partial Least Square (PLS) operated through the SmartPLS program. The results show that e-servicescape has a significant influence on customer loyalty, e-servicescape has a significant influence on perceived value, perceived value has a significant influence on customer loyalty, and perceived value mediates the relationship between e-servicescape and customer loyalty. Several suggestions and directions are also provided to expand research as a discussion topic.